O paradygmacie polskiego imperatywu - Holvoet, Axel (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
The article deals with the status of the Polish hortative forms with niech and their relationship to the imperative. Particular attention is paid to the 1st person forms, which are “interpretive” in the sense given to this term by Sperber and Wilson, viz. they echoically refer to directive speech acts issued by persons other than the speaker. The notion of interpretive hortative expressions provides an explanation to the position of the 1st person forms in the imperative paradigm as well as to distinctions between exclusive and inclusive 1 st person plural imperative forms.